2018
DOI: 10.1111/pde.13443
|View full text |Cite
|
Sign up to set email alerts
|

Burnlike scars: A sign suggestive of KLHL24‐related epidermolysis bullosa simplex

Abstract: Epidermolysis bullosa simplex is a group of inherited disorders with allelic and locus heterogeneity in which skin fragility and blistering within the skin occur. Mutations in KRT5 and KRT14 underlie the majority of reported cases. Mutations in KLHL24, a gene that encodes KLHL24 protein, have been reported recently to cause a generalized subtype of epidermolysis bullosa simplex, presumably by increasing the degradation of keratin 14. We describe a case of KLHL24-related epidermolysis bullosa simplex and highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…Several cases with typical signs of EB and mutations in KLHL24 have been described since then. 21 , 22 , 23 , 24 , 25 It is estimated that 5% of cases of EB S are associated with mutations in this gene. 1 The typical clinical signs of this subtype of EB S are still being characterized, as more studies and more patients are being described.…”
Section: Epidermolysis Bullosa Simplexmentioning
confidence: 99%
“…Several cases with typical signs of EB and mutations in KLHL24 have been described since then. 21 , 22 , 23 , 24 , 25 It is estimated that 5% of cases of EB S are associated with mutations in this gene. 1 The typical clinical signs of this subtype of EB S are still being characterized, as more studies and more patients are being described.…”
Section: Epidermolysis Bullosa Simplexmentioning
confidence: 99%
“…In contrast, the mutated protein KLHL24-ΔN28 is unable to undergo auto-ubiquitination and is consequently more stable. This results in excessive ubiquitination and therefore degradation of keratin 14, ultimately leading to skin fragility (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…We observed significantly reduced K14 expression the neonatal healthy-appearing skin of a KLHL24-mutated patient, and staining of skin at the age of 14 years showed normal K14 (Yenamandra et al, 2018), suggesting that KLHL24 regulation of K14 turnover may be more impaired during epidermal proliferation such as with body growth. The reported burnlike scars in patients with EBS due to KLHL24 mutations are not seen in EBS caused by mutations in other EBSassociated genes (Alkhalifa et al, 2018;He et al, 2016;Yenamandra et al, 2018). Additionally, Yenamandra et al reported an abnormal basement membrane structure with thickening and thinning of the lamina densa with re-duplications and blind offshoots typically encountered in poikiloderma, indicating other or additional skin pathology besides keratin filament fragility in basal keratinocytes in the case of perturbed KLHL24.…”
mentioning
confidence: 97%
“…In 2016, Lin et al (2016) and He et al (2016), using whole-exome sequencing, discovered dominant acting point mutations in the start codon of KLHL24 caused basal cell skin fragility. Since then, several other patients with basal EBS caused by KLHL24 mutations, all affecting the same start codon, have been reported (Alkhalifa et al, 2018;Lee et al, 2017;Yenamandra et al, 2018). KLHL24, unlike K5 and K14, is not a structural protein.…”
mentioning
confidence: 99%